The Influence of Thinking Actively in a Social Context Learning Model on Divergent Thinking Skills (Thinking Actively in a Social Context Learning Model on Divergent Thinking Ability) - Tri Murwaningsih; Muna Fauziah (International Journal of Science and Applied Science: Conference Series, 2021)
This research goal to identify the application of Thinking Actively in a Social Context learning model on divergent thinking skills in fifth-grade elementary school students. The type of quantitative research with a quasi-experimental type was adopted as the research approach. The research participants totaled 180 fifth-grade elementary school students. The research area was in Laweyan District, Surakarta. Six elementary schools participated in this study. Essay test was used as the instrument to collect data. For data analysis, prerequisite tests, normality test (Lilliefors), and homogeneity test (Bartlett test) were performed. Hypothesis testing was done by t-test. The research findings showed data that t was greater than t-table (9.07 > 1.97), so H0 is rejected. This means that Thinking Actively in a Social Context learning model influences the divergent thinking skills of elementary school students. The model provides evidence about the improvement of divergent thinking skills.